Cannabidiol: From Drug Interaction Potential to Modulation of the Gut Microbiome. (29th May 2020) - Kortubash, Igor; Skinner, Charles; Ewing, Laura; McGill, Mitchell; Kennon-McGill, Stefanie; Nookaew, Intawat; Kutanzi, Kristy; Quick, Charles; Yee, Eric; Walker, Larry; ElSohly, Mahmoud; Gurley, Bill
Abstract: Objectives: Cannabidiol (CBD) is the major non-psychotropic phytocannabinoid present in Cannabis sativa. In 2018, Congress designated select C. sativa cultivars as "hemp" removing them from the DEA's list of controlled substances. As a result, CBD-containing hemp extracts and other CBD products are now widely available and heavily marketed, yet their FDA regulatory status is still hotly debated. Further complicating the debate is CBD's vastly under-researched safety profile. Safety concerns yet to be adequately addressed include CBD's drug interaction potential and its effect on the gut microbiome. Methods: Using acetaminophen (APAP), the most commonly ingested over-the-counter pain medication, we demonstrated that CBD-rich cannabis extract (CRCE) poses a significant drug interaction risk. Results: Mice exposed to both CRCE and APAP developed severe liver injury. This hepatotoxicity, however, was not observed when either CRCE or APAP were administered separately. Importantly, this injury was observed in two different strains of mice with susceptibilities seemingly linked to sex (female) and age (older animals). Furthermore, both beneficial and adverse effects of CRCE on the gut microbiome were observed. Specifically, CRCE exposure increased the relative abundance of the beneficial gut microbe, Akkermansia muciniphila, however, an overall decrease in the relative abundance of all gut bacterial species was noted. This decrease was paralleled by numerous pro-inflammatory responses in the proximal jejunum and colon. Conclusions: Taken together, these findings raise significant concerns about the safety of widespread CBD usage and underlines the need for additional well-designed studies into its safety and efficacy. Funding Sources: NIGMS 1P20 GM109005.